2018
DOI: 10.1039/c8nj01294f
|View full text |Cite
|
Sign up to set email alerts
|

Ligand exchange reactions on citrate-gold nanoparticles for a parallel colorimetric assay of six pesticides

Abstract: A rapid parallel colorimetric method was developed for identification of six pesticides (acephate, phenthoate, profenofos, acetamiprid, chlorothalonil and cartap) via ligand exchange reactions on citrate-gold nanoparticles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…citrate is often used as intermediate ligand to functionalize NP 43,44 , it is easily exchanged to thiolated ligands and, recently, it has been also shown that it can be displaced by other non-covalent capping agents 45 , such, for instance, adenine 46 .…”
Section: Role Of Ligand On Aunp-liposomes Interactionmentioning
confidence: 99%
“…citrate is often used as intermediate ligand to functionalize NP 43,44 , it is easily exchanged to thiolated ligands and, recently, it has been also shown that it can be displaced by other non-covalent capping agents 45 , such, for instance, adenine 46 .…”
Section: Role Of Ligand On Aunp-liposomes Interactionmentioning
confidence: 99%
“…In the presence of pesticide residues and HCl (2 M), the inter-particle distance is reduced and the peak absorbance redshifts, resulting in a broadening of the absorption spectra (~650 nm). This can be explained by the displacement of citrate ions from the surface, shielding the repulsive forces between particles 36 . Furthermore, the addition of HCl lowers the pH of the surrounding medium, reducing the repulsive forces further.…”
Section: Resultsmentioning
confidence: 99%
“…However, the continuous excessive and uncontrolled use of these pesticides would result in residues of OPs in food substrates (vegetables and fruits) or environmental substrates, such as soil and water. The residues in crops would cause their accumulation in the human body due to the bioaccumulation property of OPs, thus resulting in an irreversible damage to various organs, such as the nervous system, reproductive system, and digestive system. , A variety of analytical methods have been developed for OPs detection, including chromatography, enzyme-linked immunoassay (ELISA), colorimetry, fluorescence assay (FL), and electrochemistry (EC) . Chromatographic analysis has a high accuracy and sensitivity, but it requires specialized instruments and a cumbersome sample pretreatment process, which are costly and time-consuming.…”
Section: Introductionmentioning
confidence: 99%